Selection of Exotic Pine Species on the Basis of their Reproductive Adaptability for Afforestation Programme in Kumaun Himalaya - Sahai, Kanak (Indian Forester, 1996)
Investigation for the selection of the fast growing exotic pine species were made on the basis of their reproductive adaptability in the Subtropical region of Kumaun Himalaya. It was found that Pinus potula is the best performing species followed by P. greggii and P. thunbergii. Therefore these species can be used for seed orchard formation and afforestation programme in the dry exposed rocky areas of Kumaun Himalaya.